2019
DOI: 10.3389/fcvm.2019.00119
|View full text |Cite
|
Sign up to set email alerts
|

High Blood Pressure Prevalence, Awareness, Control, and Associated Factors in a Low-Resource African Setting

Abstract: Background and Objectives: Recent and contextualized data are needed to improve hypertension management known as a major cardiovascular disease risk factor regardless of the geographical area. This study aimed at assessing the prevalence of hypertension, awareness of hypertensive status, treatment, and control of hypertension as well as assessing the factors associated with risk of hypertension and awareness of hypertensive status in the population of Ngaoundere. Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…This prevalence is nearly similar to a previous study done in public hospitals in Addis Ababa and Tigray Ethiopia 63% [16], Jimma 57.8% [6], Iran 61.1% [19] and South Africa 56.8% [20]. Contrary to this, the prevalence was lower to what was reported in a study conducted at Zewditu memorial hospital 73.8% [17], Jigjiga 66% [21], Addis Ababa primary health care facilities 69% [8], Cameron 69.44% [22], Zimbabwe 67.2%, and Kenya 66.6% [23]. The possible reason for this difference is explained by inclusion criteria that those studies include patients with other associated comorbid illness.…”
Section: Association Of Blood Group With Anthropometric Measurementssupporting
confidence: 82%
“…This prevalence is nearly similar to a previous study done in public hospitals in Addis Ababa and Tigray Ethiopia 63% [16], Jimma 57.8% [6], Iran 61.1% [19] and South Africa 56.8% [20]. Contrary to this, the prevalence was lower to what was reported in a study conducted at Zewditu memorial hospital 73.8% [17], Jigjiga 66% [21], Addis Ababa primary health care facilities 69% [8], Cameron 69.44% [22], Zimbabwe 67.2%, and Kenya 66.6% [23]. The possible reason for this difference is explained by inclusion criteria that those studies include patients with other associated comorbid illness.…”
Section: Association Of Blood Group With Anthropometric Measurementssupporting
confidence: 82%
“…Similar observations were made by Zekewos et al ( 49 ) who reported that age advancement, BMI (≥25.0 kg/m 2 ), and central obesity (waist-to-height ratio ≥0.50) were positively associated with hypertension. Mbouemboue and Ngoufack ( 50 ) also reported that in a low-resource African setting, age, overweight and high serum triglyceride level were identified as independent factors predicting hypertension. The observation of Mahmood et al ( 51 ) that in addition to age, education was an independent risk factor of hypertension for urban participants living in India, was not confirmed in the current study; however, adults residing in a rural area, with higher education levels were three times more likely to have CVDs; this can possibly be attributed to higher employment and income levels that can lead to unhealthy eating habits due to a higher intake of fast foods ( 6 ).…”
Section: Discussionmentioning
confidence: 90%
“…Although, this situation may rapidly change due to, urbanization, and increasing rise of the prevalence of CVD risk factors and the alarming low level of awareness of these risk factors in the Ngaoundere locality [17]. In previous studies we showed that awareness of hypertension, diabetes and dyslipidemias was poor in our locality, and even among the aware, control were suboptimal [17,18].…”
Section: Discussionmentioning
confidence: 64%